Pengaruh NPM, Market Share, TATO terhadap Nilai Perusahaan pada Industri Plastik dan Kemasan - Wulandari, Wulandari; Carmidah, Carmidah; Esty Apridasari (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
A company's value, which reflects its condition and performance, serves as a competitive element in attracting investors. Therefore, companies are required to continuously improve their net profit margin, expand their market reach, and maximize the effectiveness of asset utilization to increase company value. This research aims to explore the influence of net profit margin, market share, and total asset turnover on company value. The approach used is a quantitative method, focusing on the plastics and packaging industry subsector listed on the Indonesia Stock Exchange. Of the 14 companies included in the population, 12 companies were selected for the 2021–2024 period using purposive sampling. Data processing was carried out using panel data through Eviews 12 software. The research findings show that net profit margin has a significant impact on company value. Meanwhile, market share and total asset turnover did not show a significant effect. Thus, it can be confirmed that net profit margin plays a more dominant role in determining company value than the other two variables. These results emphasize that companies in the plastics and packaging subsector should focus their strategies on increasing profits, as a means of strengthening investor interest while maintaining the sustainability of company value in the capital market.